2021
DOI: 10.3389/fendo.2021.708494
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk of Antidiabetic Agents for Type 2 Diabetes With COVID-19: A Systematic Review and Meta-Analysis

Abstract: AimsWe conducted a systematic review and meta-analysis to assess various antidiabetic agents’ association with mortality in patients with type 2 diabetes (T2DM) who have coronavirus disease 2019 (COVID-19).MethodsWe performed comprehensive literature retrieval from the date of inception until February 2, 2021, in medical databases (PubMed, Web of Science, Embase, and Cochrane Library), regarding mortality outcomes in patients with T2DM who have COVID-19. Pooled OR and 95% CI data were used to assess relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
2
14

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 57 publications
4
81
2
14
Order By: Relevance
“…In Kan and colleagues’ article ( 1 ) the authors did not perform meta-analysis to assess the association between use of SGLT2i and GLP1RA and risk of COVID-19 mortality since they included only one SGLT2i study ( 7 ) and two GLP1RA studies ( 9 , 10 ). On the contrary, we conducted meta-analysis respectively based on 6 SGLT2i studies ( 2 7 ) and 6 GLP1RA studies ( 2 , 3 , 6 , 8 10 ), and accordingly revealed the significant association of SGLT2i use with a 22% reduction in COVID-19 mortality risk, and of GLP1RA use with a 25% reduction in that risk.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Kan and colleagues’ article ( 1 ) the authors did not perform meta-analysis to assess the association between use of SGLT2i and GLP1RA and risk of COVID-19 mortality since they included only one SGLT2i study ( 7 ) and two GLP1RA studies ( 9 , 10 ). On the contrary, we conducted meta-analysis respectively based on 6 SGLT2i studies ( 2 7 ) and 6 GLP1RA studies ( 2 , 3 , 6 , 8 10 ), and accordingly revealed the significant association of SGLT2i use with a 22% reduction in COVID-19 mortality risk, and of GLP1RA use with a 25% reduction in that risk.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, we conducted meta-analysis respectively based on 6 SGLT2i studies ( 2 7 ) and 6 GLP1RA studies ( 2 , 3 , 6 , 8 10 ), and accordingly revealed the significant association of SGLT2i use with a 22% reduction in COVID-19 mortality risk, and of GLP1RA use with a 25% reduction in that risk. Moreover, Kan et al’s meta-analysis ( 1 ) did not include 8 recently-published DPP4i studies ( 2 4 , 8 , 11 14 ), which limited its statistical power. Accordingly, a statistically significant difference between DPP4i and Non-DPP4i was not observed in that meta-analysis ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations